Nonconventional diabetes-related care strategies for patients with chronic kidney disease: A scoping review of the literature. (27th February 2019) - Clemens, Kristin K; Kalatharan, Vinusha; Ryan, Bridget L; Reichert, Sonja
Background: Patients with diabetes and chronic kidney disease (CKD) are at high risk of diabetes-related complications. Diabetes care can support these individuals, but outpatient clinic appointments can be difficult to attend, given their already high burden of multimorbidity. Methods: We systematically searched the medical and grey literature for studies that evaluated the effect of nonconventional diabetes care strategies on diabetes-related outcomes in adults with stages 2–5 CKD or using dialysis (end of search December 30, 2017). We included both randomized-controlled trials and observational studies. Study selection and data extraction were completed by two independent reviewers. Diabetes-related outcomes included glycemic, blood pressure, and lipid control, along with microvascular complications, macrovascular complications, and death. Results: After screening 2177 relevant citations, we identified 34 studies which met inclusion. The majority were observational studies. Studies were frequently small, single-centered, and excluded patients with more advanced CKD. Nonconventional diabetes care strategies included community-based care, unique self-management and education programs, nurse-led care clinics, dialysis-based diabetes programs, telemedicine, and interdisciplinary care clinics. Programs were most often developed by study investigators. Although there were limitations to several of the included studies, programs were described to have modest effects on physiologic outcomes, and in some cases, diabetes-related complications and death. Conclusions: Nonconventional diabetes-related care might be helpful to patients with CKD. Prior to developing and implementing programs, however, it will be important to study them more rigorously, understand their acceptability to patients, and evaluate their costs and feasibility in a real-world setting.